High Nd3+→Yb3+ energy transfer efficiency in tungsten-tellurite glass: A promising converter for solar cells - Costa, Francine Bettio [UNESP]; Yukimitu, Keizo [UNESP]; Nunes, Luiz Antonio de Oliveira; Figueiredo, Marcio da Silva; Silva, Junior Reis; Andrade, Luis Humberto da Cunha; Lima, Sandro Marcio; Moraes, João Carlos Silos [UNESP] (Wiley, 2017)
This work reports on the energy transfer efficiency for Nd3+/Yb3+ co-doped tellurite glasses (80TO2-20WO3, in mol%,). The correlation between Yb3+ ion concentration and the downconversion mechanism was investigated using optical and thermal lens spectroscopies, which enabled investigation of the radiative and nonradiative processes, respectively, involved in energy transfer from neodymium to ytterbium. The Nd3+ near-infrared fluorescence disappeared almost entirely when the maximum concentration of Yb3+ ions (4 mol%) was doped into the host. In contrast, there was a corresponding increase in the ytterbium emission at around 980 nm. When ytterbium was added, there was also a simultaneous reduction in the amount of heat generated by the sample due to a reduction in the nonradiative decay rate, corroborating the suspected high energy transfer efficiency of Nd3+→Yb3+. The results indicate that tungsten-tellurite glasses may be of potential use in solar cells for matching the solar emission spectrum to the semiconductor cell.
Keywords: downconversion process; energy-transfer efficiency; optical spectroscopy; Tellurite glasses; thermal lens spectroscopy